Optics and Biophotonics in Low-Resource Settings IX 2023
DOI: 10.1117/12.2649030
|View full text |Cite
|
Sign up to set email alerts
|

A compact fluorescence sensor for low-cost non-invasive monitoring of gut permeability in undernutrition

Abstract: Undernutrition is associated with approximately 45% of deaths among children under the age of 5. Furthermore, in 2020, around 149 million children suffered impaired physical/cognitive development due to lack of adequate nutrition. Environmental enteropathy (EE) is associated with undernutrition and is characterized by a multifaceted breakdown in gut function, including an increase in intestinal permeability that can lead to inflammatory responses. However, the role and mechanisms associated with EE (partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…As such, our ongoing and future work now involves deploying transcutaneous spectroscopy in clinical studies of IBD and undernutrition (see preliminary results reported in Ref. 25 ) to further investigate the potential for non-invasive assessment of gut function.…”
Section: Resultsmentioning
confidence: 99%
“…As such, our ongoing and future work now involves deploying transcutaneous spectroscopy in clinical studies of IBD and undernutrition (see preliminary results reported in Ref. 25 ) to further investigate the potential for non-invasive assessment of gut function.…”
Section: Resultsmentioning
confidence: 99%